2015
DOI: 10.1016/j.nmd.2015.06.451
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of disease progression in type 2 and 3 SMA: Implications for clinical trials

Abstract: The aim of the study was to establish 12-month changes in the Hammersmith Functional motor scale in a large cohort of SMA patients, to identify patterns of disease progression and the effect of different variables. 268 patients were included in this multicentric study. Their age ranged between 2.5 and 55.5 years at baseline, 68 were ambulant and 200 non-ambulant. The baseline scores ranged between 0 and 66 (mean 23.91, SD 20.09). The 12-month change was between −14 and +9 (mean −0.56, SD 2.72). Of the 268 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
105
2
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(129 citation statements)
references
References 0 publications
13
105
2
9
Order By: Relevance
“…Similarly, no such tendency was observed in the two clinical motor scales applied in this study. Both MFM and 6MWT remained stable within the observed period, which corroborates the findings of other longitudinal studies exploring established clinical scales in which changes of functional outcome in Type II and III SMA patients over 1 year are of small magnitude . Nevertheless, our results suggest that, even though the progression of ambulant Type III SMA patients is relatively slow and no increase in intramuscular fat accumulation was detectable over 1 year, the qMRI indices – namely T 2 and FF – demonstrated a high potential to serve as novel quantitative outcome measures in clinical trials complementing traditionally administered functional motor scales.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, no such tendency was observed in the two clinical motor scales applied in this study. Both MFM and 6MWT remained stable within the observed period, which corroborates the findings of other longitudinal studies exploring established clinical scales in which changes of functional outcome in Type II and III SMA patients over 1 year are of small magnitude . Nevertheless, our results suggest that, even though the progression of ambulant Type III SMA patients is relatively slow and no increase in intramuscular fat accumulation was detectable over 1 year, the qMRI indices – namely T 2 and FF – demonstrated a high potential to serve as novel quantitative outcome measures in clinical trials complementing traditionally administered functional motor scales.…”
Section: Discussionsupporting
confidence: 87%
“…An international effort has recently been made to define trajectories of progression by using a large dataset combining data from large networks in US, UK and Italy. This effort confirmed that, using the Hammersmith Functional Motor Scale Expanded (HFMSE), the changes over 1 year are minimal but that different trajectories of progression can be identified [38]. Non-ambulant patients tend to improve before reaching the age of 5 years while after this age they will tend to show some decline.…”
Section: Topics Discussed 211 Setting the Framework: 1 Natural Hisupporting
confidence: 60%
“…Recent studies, using motor and developmental assessments, have also explored longitudinal changes in motor function, showing how this continues to decline after diagnosis. At symptom onset type 1 infants generally have reduced motor skills, the majority will have no head control, and new motor skills are never subsequently achieved [38]. Thus, prolonged survival, with nutritional and ventilation support, does not enhance motor development.…”
Section: Topics Discussed 211 Setting the Framework: 1 Natural Himentioning
confidence: 99%
“…those with moderate improvement). A study by Mercuri et al [43] reported that an increase of greater than two points was unlikely in patients with later-onset SMA. In addition, patients and caregivers considered a 1-point increase or even stabilisation as meaningful.…”
Section: Later-onset Spinal Muscular Atrophymentioning
confidence: 99%